Potential protective benefits of Schisandrin B against severe acute hepatitis in children during the COVID-19 pandemic based on a network pharmacology analysis - Fang, Yanhua; Zhang, Lingling; Wang, Zhe; Wang, Ruoyu; Liang, Shanshan (Frontiers in Pharmacology, 2022)
Aims: Reports of hepatitis in children during the COVID-19 outbreak received attention from all across the world. The most likely offenders are adenovirus and SARS-CoV-2. At this moment, the best option for symptomatic treatment is a combination of anti-COVID-19 and hepatitis symptom relievers. Schisandrin B (SchB) has long been recognised to have liver-protective characteristics, and anti-COVID-19 properties were recently identified. In the case of COVID-19 with hepatitis of unknown origin, we used network pharmacology to explore the symptomatic therapy and protective effects of SchB. Main methods: SwissTargetPrediction projected SchB's potential targets. The GeneCards, NCBI, and OMIM databases were used to compile information on the diseases hepatitis, adenovirus, and SARS-CoV-2. Following the use of a Venn diagram viewer to identify intersection genes, a PPI network was constructed and the core genes were identified. GO and KEGG enrichment, as well as molecular docking, were employed to highlight the mechanisms of SchB on hepatitis. Key findings: SchB contains 27 targets on Adenovirus_hepatitis and 16 targets on SARS-CoV-2_hepatitis, with 12 genes shared between the two viruses. Both target populations clustered in viral infection and cancer pathways, as well as in processes like kinase activity phosphatase, cell adhesion and ATPase binding. These might be closely related to liver damage and membrane binding from adenovirus or SARS-CoV-2 infections. Surprisingly, the Top 5 targets of SchB_SARS-CoV-2_hepatitis and SchB_Adenovirus_hepatitis were also similar, frequently sharing EGFR, HSP90AA1, and MAPK1. Significance: These findings imply that SchB may offer similar protection targets and mechanisms against acute hepatitis caused by an adenovirus or by SARS-CoV-2 in children during the COVID-19 pandemic.